Local Closure Functions in Hereditary Generalized Topological Spaces (Journal of Informatics and Mathematical Sciences, 2018)
In this paper, we introduce and study the notions of local closure functions and also we introduce the operator \(Ψ_Γ\) in hereditary generalized topological spaces.
Keywords: Generalized topology; Hereditary generalized topological spaces; Local closure function